Nostalgia Marketing: A Systematic Literature Review Using the Research Onion Framework - Benni Ahdiyana Pamungkas; Cristian Hadi Pranata (Riviera Publishing, 2026)
This study aims to identify future research directions and opportunities in nostalgia marketing through the Systematic Literature Review (SLR) using the Research Onion framework. A total of 22 Scopus-indexed articles were screened following PRISMA guidelines, of which 11 articles were selected for in-depth analysis based on research philosophy, approaches, methods, strategies, time horizons, and data analysis techniques. The findings indicate that nostalgia marketing is grounded in two paradigms, interpretivism and positivism, with a relatively balanced use of inductive and deductive approaches. They employ qualitative, quantitative, and mixed-method designs, utilizing diverse strategies such as literature reviews, case studies, surveys, and experiments. Cross-sectional designs are found to be the most commonly adopted time horizon. This study provides a comprehensive overview of the methodological landscape of nostalgia marketing and highlights key directions for future inquiry. The findings offer valuable implications for both researchers and practitioners by demonstrating how nostalgia-driven strategies can be effectively leveraged across industries. Furthermore, this study lays an initial foundation for the development of theoretical models of nostalgia marketing, particularly in the Indonesian context.